Raman spectroscopy for cancer detection and cancer surgery guidance: translation to the clinics. Issue 17 (20th July 2017) - Santos, Inês P.; Barroso, Elisa M.; Bakker Schut, Tom C.; Caspers, Peter J.; van Lanschot, Cornelia G. F.; Choi, Da-Hye; van der Kamp, Martine F.; Smits, Roeland W. H.; van Doorn, Remco; Verdijk, Rob M.; Noordhoek Hegt, Vincent; von der Thüsen, Jan H.; et al.
Abstract : This review summarizes actual clinical needs in oncology that can be addressed by Raman spectroscopy, provides results published in the last 10 years and analyses the current status of translation of these results into clinical practice. Abstract : Oncological applications of Raman spectroscopy have been contemplated, pursued, and developed at academic level for at least 25 years. Published studies aim to detect pre-malignant lesions, detect cancer in less invasive stages, reduce the number of unnecessary biopsies and guide surgery towards the complete removal of the tumour with adequate tumour resection margins. This review summarizes actual clinical needs in oncology that can be addressed by spontaneous Raman spectroscopy and it provides an overview over the results that have been published between 2007 and 2017. An analysis is made of the current status of translation of these results into clinical practice. Despite many promising results, most of the applications addressed in scientific studies are still far from clinical adoption and commercialization. The main hurdles are identified, which need to be overcome to ensure that in the near future we will see the first Raman spectroscopy-based solutions being used in routine oncologic diagnostic and surgical procedures.